The Effect of Discipline and Working Environment on Employee Performance with Job Satisfaction as Intervening Variable: The Case of PT Gapura Medika Vetisia - Rahmad Saidi; Fadhil Yamaly; Tobari Tobari (International Journal of Marketing & Human Resource Research, 2026)
This study aims to determine 1) the Effect of Work Discipline on Job Satisfaction at PT Gapura Medika Vetisia. 2) The Effect of the Work Environment on Job Satisfaction at PT Gapura Medika Vetisia. 3) The Effect of Work Discipline on Employee Performance at PT Gapura Medika Vetisia. 4) The Effect of the Work Environment on Employee Performance at PT Gapura Medika Vetisia. 5) The Effect of Job Satisfaction on Employee Performance at PT Gapura Medika Vetisia. This research is associative. The population of this study comprised all 132 employees, and the sample size was 120. The sampling technique used was cluster sampling. The data used in this study were primary data collected using a questionnaire. The data analysis technique used was Structural Equation Modeling (SEM) with the LISREL program. The results of this study indicate that: 1) there is an effect of work discipline on job satisfaction. 2) There is a significant effect of the work environment on job satisfaction. 3) There is a significant effect of work discipline on performance. 4) There is a significant effect of the work environment on performance. 5) There is a significant effect of job satisfaction on performance. Job satisfaction strengthens the influence of work discipline and work environment on employee performance at PT Gapura Medika Vetisia.